O director de turma: líder e facilitador da relação educativa - Mendonça, Carlos Filipe Gomes Carrajola de (2009)
The need of knowledge and reflection on models and practices of organization and school managing is increasingly a prerequisite for the development process and the improvement of the performance of schools. This recognition demands an investment in the training of teachers in general, and especially those who have responsibilities within the intermediate management of schools. In its internal organization, the school has several levels of intervention. The emphasis of our study lies in the meso level of intervention, since it is at this level that the action of the class director fits. This intermediate manager is presented as a true leader, appealing, in the exercise of his functions, to a set of skills that allow him the adoption of a style of leadership more appropriate to the groups he leads, that is, the class council and the class itself. Aspects such as the educational relationship that is established between teachers and students can be improved as a result of his action, which is the study object of the study that follows. This is an exploratory study that investigates the influence of the class director on the quality of relationships established in the context of the group he leads. The results obtained indicate that, despite the awareness of the importance of his position in a learning organization, there are doubts as to his efficient performance, attributable to the awkwardness that teachers show in playing a role and a leadership function to others that, professionally, are their peers.